Association between atrial fibrillation and white blood cell count after the Great East Japan Earthquake: An observational study from the Fukushima Health Management Survey. Issue 6 (12th February 2021) - Suzuki, Hitoshi; Ohira, Tetsuya; Takeishi, Yasuchika; Sakai, Akira; Hosoya, Mitsuaki; Yasumura, Seiji; Kawasaki, Yukihiko; Takahashi, Atsushi; Nakano, Hironori; Kamiya, Kenji
Abstract : Abstract: We had earlier reported about the increase in the prevalence of atrial fibrillation (AF) among residents in the evacuation zone of Fukushima Prefecture after the Great East Japan Earthquake. In the present investigation, we explored the association between the prevalence of AF and white blood cell (WBC) count after the earthquake through an observational cross-sectional study. A total of 14, 800 participants (6427 men and 8373 women) were included in the Fukushima Health Management Survey. For the present study, 12-lead electrocardiogram tracings and the WBC count and its subtypes were obtained and analyzed. The odds ratios (ORs) of AF after the earthquake and the 95% confidence intervals (CIs) for one standard deviation of differential WBC count were calculated after adjustments for age and other potential confounding factors using the logistic regression model. Our results revealed a prevalence of AF of 1.8% (269 participants) after the earthquake. Monocyte count and neutrophil/lymphocyte ratio exhibited a significant association with the prevalence of AF in the multivariable-adjusted model. The adjusted ORs of monocyte count and neutrophil/lymphocyte ratio for AF were 1.21 (95% CI, 1.05–1.40, P = .01) and 1.22 (95% CI, 1.01–1.44, P < .05), respectively. The prevalence of AF was associated with increased monocyte count and neutrophil/lymphocyte ratio among residents in the evacuation zone in Fukushima Prefecture, suggesting that inflammation and psychological stress could be important factors mediating the development of AF after the earthquake.